Islamic Aspects of the Legacy of Malcolm X - Samory Rashid (International Institute of Islamic Thought, 1993)
Spike Lee's 1992 film, ''Malcolm X," is the most recent evidence of the increased popularity of Malcolm X (El Haj Malik El Shabazz). The film, based on a screenplay by James Baldwin and Arnold Perl, sparked controversy over "X" memorabilia and also a debate over the appropriate interpretation of Malcolm X's legacy. For example, black nationalist Amiri Baraka opposed Lee's portrayal and criticized the film as an attempt to "make middle class Negroes sleep easier." Yet when the current controversy and debate end, the Islamic aspects will remain, as before, the most significant and least recognized elements of Malcolm X's legacy. This paper briefly examines this phenomenon in order to offer a more accurate and meaningful analysis of the significance of Malcolm X. Although Alex Haley's Autobiography of Malcolm X climbed to the New York Times' best-seller list in 1992, popular media accounts, such as Lee's film, have stimulated even greater social interest. As one writer notes, "if many blacks did not listen when he was alive, young blacks are listening now." It is also interesting to note how "Malcolm X's appeal has crossed racial barriets in a way that would have been unthinkable during his life." Nevertheless, the emergent popularity of Malcolm X in the 1990s is a direct result of the lingering presence of racism and of his own martydom in the struggle against it. Most mainstream analyses associate Malcolm X's message with vie lence and hatred of white America. For example, his oft-quoted phrase, "by any means necessary," and his advocacy of martial arts proficiency and rifle club formation for defenseless black victims of racial violence ...